Perancangan Dan Implementasi Video Media Pembelajaran Perjalanan Wisata Di SMKN 2 Batam Menggunakan Metode MDLC - Daniel Apdianto Herman; Albert Ilham Sutrisno (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
The general development of the industrial sector that is not in sync with the provision of sufficient human resources for industrial and tourism management causes a very high demand for human resources. who can judge one of the characteristics of a country's progress from the quality of its education. Because education plays a very important role in impressing the next generation of the nation, to maximize regional development, the dynamics of regional autonomy must be utilized as much as possible by local governments. With the advancement of technology, globalization has become more and more important. We know that globalization has brought many foreign cultures to Indonesia and the possibility of changing the potential of unfamiliar cultural tools. In the design and implementation of applied research at SMK Negeri 2 Batam, the author uses standard methods in making learning media for the multimedia development life cycle. as for the application of this learning video media about the learning interest of the students of SMK Negeri 2 Batam.